Neuroinflammation is a susceptibility factor in developing a PTSD-like phenotype - Shanazz, Khadijah; Nalloor, Rebecca; Lucas, Rudolf; Vazdarjanova, Almira (Frontiers in Behavioral Neuroscience, 2023)
Introduction Post-Traumatic Stress Disorder (PTSD) is a psychological disorder that occurs after a traumatic event in a subset of exposed individuals. This implies the existence of susceptibility factors that foster the development of PTSD. Susceptibility factors are present before trauma and can contribute to the development and maintenance of PTSD after trauma. Manipulation of susceptibility factors may decrease the probability of developing PTSD. A putative susceptibility factor is inflammation. Patients with PTSD have been documented to have a higher pro-inflammatory profile compared to non-PTSD subjects. In addition, they are more likely to develop and die from cardiovascular disease which has a strong inflammation component. It is not known, however, whether inflammation plays a role in developing PTSD or whether reducing inflammation can prevent PTSD. Methods We used the Revealing Individual Susceptibility to a PTSD-like phenotype (RISP) model to behaviorally classify male rats as resilient or susceptible before trauma and tested their serum and prefrontal cortical (mPFC) levels of IL-1β, IL-6, TNFα, IL-10, IFN IFNγ, and KC/GRO to determine whether inflammation represents a putative susceptibility factor for PTSD. Results We found elevated IL-6 levels in the mPFC, but not serum, of susceptible rats compared to resilient animals before trauma. Serum and mPFC levels were not correlated in any of the cytokines/chemokines. Rats with high anxiety-like behavior had elevated IL-6 and IL-10 mPFC levels. Acoustic startle responses were not associated with cytokine/chemokine levels. Discussion Neuroinflammation, rather than systemic inflammation exists in susceptible male rats before trauma and is thus a putative susceptibility factor for PTSD. Thus, susceptibility appears neurogenic in its pathogenesis. The lack of differences between susceptible and resilient rats in serum cytokine/chemokine levels infers that peripheral markers will not be useful in determining susceptibility. Chronic neuroinflammation appears more broadly associated with anxiety rather than startle responses.